1994
DOI: 10.1103/physrevlett.73.3367
|View full text |Cite
|
Sign up to set email alerts
|

Collective Expansion in Central Au + Au Collisions

Abstract: Energy spectra for intermediate mass fragments produced in central Au + Au collisions at E/A = 100 MeV indicate a collective expansion at breakup. For the first time, values for this collective expansion energy per nucleon are extracted independently for each charge. Typically, these values are one-third to one-half of the incident kinetic energy per nucleon in the c.m. system, but they decrease with Zf, suggesting that all fragments do not participate equally in the collective expansion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 74 publications
(28 citation statements)
references
References 29 publications
3
25
0
Order By: Relevance
“…One of the main results is that (62 ± 8)% of the available energy is stored into radial flow. This value is significantly larger than the values recently published by the EOS collaboration [28] , but not too far from our earlier, more preliminary analyses [40,41] and in line with, although somewhat larger than values from analyses reported in [20][21][22]. The associated average flow velocity < β f > is also given in the Table. In the following we shall present a sample of our data and use the blast model fits as reference.…”
Section: Experimental Data and The Blast Modelsupporting
confidence: 71%
See 2 more Smart Citations
“…One of the main results is that (62 ± 8)% of the available energy is stored into radial flow. This value is significantly larger than the values recently published by the EOS collaboration [28] , but not too far from our earlier, more preliminary analyses [40,41] and in line with, although somewhat larger than values from analyses reported in [20][21][22]. The associated average flow velocity < β f > is also given in the Table. In the following we shall present a sample of our data and use the blast model fits as reference.…”
Section: Experimental Data and The Blast Modelsupporting
confidence: 71%
“…Older exclusive information on heavy cluster formation from Bevalac times was limited to an experiment at 200 A MeV [15] concentrating on sideflow: a remarkable result of this study was the demonstrated higher sensitivity of the IMF's to flow, a fact that had been anticipated in the framework of hydrodynamical model calculations [16]. Since then, new information from central or semicentral collisions at energies beyond 100 A MeV has emerged from work done both at Berkeley and Darmstadt [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…The largest fragment multiplicities measured so far were observed in central 197 Au on 197 Au collisions at a bombarding energy of 100 MeV per nucleon [80]. The analysis of the kinetic energy spectra in these reactions has revealed a considerable collective outward motion (radial flow), superimposed on the random motion of the constituents at the breakup stage [83]. The associated collective energy constitutes up to one-half of the incident kinetic energy in the center-of-mass frame and increases approximately linearly over the range of bombarding energies up to 1000 MeV per nucleon [84].…”
Section: Discussionmentioning
confidence: 96%
“…Alternatively, temperature may be obtained through isotopic thermometers. The double isotope thermometer has provided much data [23][24][25]; however, the 'Corresponding author: fszhang@bnu.edu.cn temperatures derived are complicated by model-dependent secondary decay corrections [25][26][27],…”
Section: Introductionmentioning
confidence: 99%